1986
DOI: 10.1056/nejm198608143150704
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem and Reinfarction in Patients with Non-Q-Wave Myocardial Infarction

Abstract: We performed a multicenter, double-blind, randomized study to evaluate the effect of diltiazem on reinfarction after a non-Q-wave myocardial infarction. Nine centers enrolled 576 patients: 287 received diltiazem (90 mg every six hours) and 289 received placebo. Treatment was initiated 24 to 72 hours after the onset of infarction and continued for up to 14 days. The primary end point, reinfarction, was defined as an abnormal reelevation of MB creatine kinase in plasma within 14 days. Reinfarction occurred in 27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 503 publications
(70 citation statements)
references
References 50 publications
1
69
0
Order By: Relevance
“…The largest of these trials is the DAnish Verapamil Infarction Trial (DAVIT), which showed a trend in reducing the outcomes of death or nonfatal MI in 3447 patients with suspected acute coronary syndromes administered intravenous verapamil at admission and then orally for 1 week. 112 In the Diltiazem Reinfarction Study (DRS), 113 576 patients were treated with diltiazem or placebo 24 to 72 hours after the onset of non-Q-wave MI. There was a significant reduction in reinfarction and refractory angina at 14 days.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…The largest of these trials is the DAnish Verapamil Infarction Trial (DAVIT), which showed a trend in reducing the outcomes of death or nonfatal MI in 3447 patients with suspected acute coronary syndromes administered intravenous verapamil at admission and then orally for 1 week. 112 In the Diltiazem Reinfarction Study (DRS), 113 576 patients were treated with diltiazem or placebo 24 to 72 hours after the onset of non-Q-wave MI. There was a significant reduction in reinfarction and refractory angina at 14 days.…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…A benefit was not proved, but death or nonfatal MI tended to be reduced. The Diltiazem Reinfarction Study (DRS) studied 576 patients with UA/NSTEMI (329). Diltiazem reduced reinfarction and refractory angina at 14 d without an increase in (322,336), whereas those excluding nifedipine (e.g., for verapamil alone) have reported favorable effects on outcomes (332).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…Diltiazem reduced reinfarction and refractory angina at 14 d without an increase in (322,336), whereas those excluding nifedipine (e.g., for verapamil alone) have reported favorable effects on outcomes (332). Retrospective analyses of DAVIT and MDPIT suggested that verapamil and diltiazem can have a detrimental effect on mortality rates in patients with LV dysfunction (329,330). In contrast, verapamil reduced diuretic use in DAVIT-2, (333).…”
Section: Calcium Channel Blockersmentioning
confidence: 99%
“…[21][22][23][24][25] The practice of measuring CK-MB enzymes in high. risk elective postoperative surgical patients with interpretable ECGs appears to have evolved from coronary care guidelines for investigation of symptomatic chest pain with non-diagnostic ECGs; and a desire not to miss a clinically relevant event (myocardial infarction) ha a population of patients at risk for the event, and for whom considerable morbidity occurs if a myocardial infarction is manifest.…”
Section: Discussionmentioning
confidence: 99%